The Role of Natural Cytotoxicity Receptors in Various Pathologies: Emphasis on Type I Diabetes - Mandelboim, Ofer; Enk, Jonatan (Frontiers in Immunology, 2014)
Natural killer (NK) cells are innate immune lymphocytes that function mainly as immune sentinels against viral infection and tumorogenesis. NK cell function is governed by inhibitory and activating signals arising from corresponding receptors. A prominent group of activating NK receptors is the natural cytotoxicity receptors (NCRs) which include NKp30, NKp44 and NKp46. These receptors bind various diverse ligands of pathogenic, tumor and even self origin. Type 1 diabetes mellitus (T1D) is a multifactorial autoimmune disease, in which insulin producing beta (β) cells are ablated by the immune system. This killing of β is carried out mainly by T cells, but many other immune cells have been implicated in the pathogenesis of this disease. Importantly, NK cells were shown to be key participants in the initial autoimmune attack. It was shown that all β cells from humans and mice, healthy or sick, express an unknown ligand for the activating NKp46 receptor. In this review we describe the role played by the NCRs in various pathologies with emphasis on type I diabetes.